Effect of post-exercise whole body vibration with stretching on mood state, fatigue, and soreness in collegiate swimmers - Merrigan, J. J.; Tynan, M. N.; Oliver, J. M.; Jagim, A. R.; Jones, M. T. (Sports, 2017)
Static stretching (SS) during whole body vibration (WBV) has been suggested for exercise recovery. The purpose was to compare post-exercise self-ratings of fatigue (FAT), mood state (BAM), soreness (SOR), and perceived exertion (RPE) between SS and WBV+SS in swimmers (9 women, mean ± SD: 19.3 ± 1.3 year, 171 ± 5.7 cm, 67.6 ± 7.2 kg, 26.6 ± 4.1 %body fat (%BF); 10 men, mean ± SD: 19.7 ± 1.0 year, 183 ± 5.5 cm, 77.1 ± 4.2 kg, 13.1 ± 2.2 %BF). Athletes were divided by sex, event (sprint, distance), and assigned to SS or WBV+SS. Both conditions consisted of SS performed on the WBV platform with or without WBV (50 Hz, 6 mm). Sessions consisted of: pre and post measures of BAM, FAT, SOR; the condition; and RPE. Mixed factorial ANOVA were run. A significant condition by pre/post interaction was observed (p = 0.035). Post hoc analyses showed WBV+SS elicited lower post-exercise ratings of FAT (p = 0.002) and the BAM affective states, of tension (p = 0.031), and fatigue (p = 0.087). RPE did not differ between conditions. Of interest is the decrease in tension and fatigue noted by the BAM. Mood state can be indicative of how athletes adapt to training volume and intensity.